Seismic vulnerability of jacket supported large offshore wind turbine considering multidirectional ground motions. (September 2022) - James, Maria; Haldar, Sumanta
Abstract: Large numbers of offshore wind turbines in earthquake prone areas increase the scientific interest in analysing their seismic vulnerability. This study investigates the deformation and collapses susceptibility of a 10 MW jacket supported offshore wind turbine (OWT) considering different geometry of pile and jacket. A three-dimensional finite element model of the soil-pile-jacket-tower is developed in ABAQUS. A performance-based analysis is conducted to quantify the engineering demand parameters by choosing first mode spectral acceleration as the intensity measure for different pile length-to-diameter ratios and the base width of the jacket. The significance of considering higher modes and the vertical component of the earthquake motion on the dynamic response of offshore wind turbines is also discussed. Considerable amplification of acceleration is observed at the nacelle due to vertical excitation. In low to moderate earthquake shaking, jacket base width shows a marginal influence on the responses, while a significant impact is observed for strong earthquake shaking. Mudline rotation and acceleration response at the nacelle are the most critical parameters that govern the design under the serviceability limit state. Moreover, it is observed that initiation of the rocking mode of vibration for jacket-supported OWTs resting on a pile foundation is significantly less until its embedment length reduces considerably (3 to 5 m).